Librarian Work Stress at The Library of Universitas Hasanuddin Makassar - Gunandar, M. Agus; Iskandar, Iskandar; Ismail, Wahyuni; Ahmad, La Ode Ismail (International Journal of Islamic Studies, 2023)
This article discusses the work stress for librarians at the library of Universitas Hasanuddin Makassar. The purpose of this study are; a) to find out the work stress in the library of Universitas Hasanuddin Makassar. b) to find out the factors contributing to the work stress of the librarians at Universitas Hasanuddin Makassar. This study employs mixed-methods research that refers to qualitative and quantitative. The data collection methods were carried out through observation, interviews, and questionnaires, so that the data from the research site could be described descriptively. Data processing and analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and data verification or drawing conclusions. The results of this study show that a) The work stress of the librarians at Universitas Hasanuddin Makassar has three symptoms, namely: the most dominant psychological symptoms that the librarians experience are confusion, tension, solitaryness, and decreased concentration; the most common physiological symptoms felt by librarians are fatigue and headaches; and the behavioral symptoms refer to the lack of socialization with friends and procrastination of work. b) The importance of undertaking stress management to minimize the factors causing work stress that can affect librarians, their work, and the work environment. The implementation of stress management is expected to create a healthy work environment in the library at Universitas Hasanuddin Makassar.